1997
DOI: 10.1093/sleep/20.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Sleep and Arousals During Bedsharing With Infants

Abstract: Contrary to popular perception, studies show that parent-infant bedsharing is not uncommon in American society. A belief that bedsharing with infants negatively impacts the quality of adult sleep also appears wide-spread. This has not been substantiated, however, because the few studies that have measured the impact of bedsharing on adult sleep examined only bedsharing with another adult. In the present study, laboratory polysomnography was performed in 20 routinely bedsharing and 15 routinely solitary-sleepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
74
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 0 publications
3
74
0
Order By: Relevance
“…We recently reported, in these same mother-infant pairs, that mothers aroused 30% more often when they bed shared than when they slept alone. 29 Furthermore, the present results demonstrated an approximate doubling on the bed sharing night in the temporal overlap of infant with maternal arousals. Given that the largest increase in overlapping arousals by far reflected instances where the infant aroused first, these findings imply a high level of responsivity on the mother's part to the infant that did not habituate with routine bed sharing.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…We recently reported, in these same mother-infant pairs, that mothers aroused 30% more often when they bed shared than when they slept alone. 29 Furthermore, the present results demonstrated an approximate doubling on the bed sharing night in the temporal overlap of infant with maternal arousals. Given that the largest increase in overlapping arousals by far reflected instances where the infant aroused first, these findings imply a high level of responsivity on the mother's part to the infant that did not habituate with routine bed sharing.…”
Section: Discussionsupporting
confidence: 60%
“…Some have been discussed in detail previously 29,30 and include the small bed size used for bed sharing and limitations on the extent to which the results would generalize to other subject populations. It is unlikely that a passive effect of bed size alone explains the facilitation of infant arousals with bed sharing, given (a) the close face-to-face proximity maintained by mothers, 50 (b) the observations that mothers typically managed the infant's position relative to her during periods of breastfeeding, often actively enclosing the infant within their arms (unpublished observations), and (c) that mother-infant bed sharing in a single bed (or couch of similar size) is probably not an uncommon occurrence in the population we sampled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, on the cosleeping nights, infants did tend to wake up more often, but the lack of difference in the total amount of time awake demonstrated that their awakenings were briefer than those of the infants who slept alone. 17 Complementary to the results reported by Mosko and colleagues, 17 when routinely cosleeping infants sleep alone, they display fewer awakenings and more time in quiet sleep at 6 months of age. 19 Mosko and colleagues 20 also have reported on the proximity and positioning of mothers and their 11-15-week-old infants during bedsharing nights.…”
Section: Introductionsupporting
confidence: 52%
“…In this paper we present the results of a study investigating how behavioural variables such as feeding choice and partner presence in the bed may affect mother-infant sleep behaviour and therefore infant sleep safety. Comparison is made with the detailed observations of mother-infant bed-sharing 6 behaviour from McKenna and Mosko"s studies of breastfeeding Latina mothers and their babies (McKenna 1990;McKenna and Mosko 1994;McKenna, et al 1997;Mosko et al 1996;Mosko, et al 1997a;Mosko et al 1997b;Mosko et al 1997c;Richard et al 1997). These studies were conducted in a hospital sleep lab in California using polysomnographic monitoring and video observations of both mothers and infants sleeping together in a narrow hospital bed.…”
Section: Introductionmentioning
confidence: 97%